Identity crisis of nanostructures inside the human body: a perspective on inflammation - Saha, Sarmistha; Saso, Luciano (Frontiers in Nanotechnology, 2023)
Advances in nanotechnology have attracted a lot of potential medical applications, such as therapeutic agents, diagnostics, and theranostics for complex diseases. The intersection of nanotechnologies, molecular and cell biology, and medicine can function to improve human health and quality of life, making healthcare a primary target of nanotechnology research. However, this seems like a promising future, ethical, health, and safety concerns must be considered before a reasoned evaluation of the situation can be made. Most nanostructures, however, typically fail to reach their intended targets because they get trapped inside innate immune cells. Since little is known about how nanomaterials and nanotechnologies change their identity inside the biological system, there is a wide-ranging discussion on possible concerns. In this regard, we present a perspective on how biological systems may interact with nanoscale materials and how that interaction might affect cellular recognition of nanostructures. We will also discuss dynamic modifications of the nanomaterials inside biological systems and, in particular, inflammation responses.